Sedekah Kupat: The Socio-Cultural Representation and Solidarity of the Wanareja Community, Cilacap - Nuraini, Siti; Brata, Yat Rospia; Sudarto, Sudarto (Universitas Galuh, 2025)
The Sidekah Kupat tradition in Wanareja, Cilacap, represents a cultural heritage that embodies the harmony between humans, nature, and social values. This study aims to analyze the symbolic meaning, social solidarity, and ecological function of this tradition by applying Durkheim’s mechanical-organic solidarity, Mead’s symbolic interactionism, Malinowski’s functionalism, and Koentjaraningrat’s cultural theory. Using a historical method with an ethnographic approach, the study involved topic selection, heuristics, source criticism, interpretation, and historiography. Data were collected through participatory observation, in-depth interviews, and documentation. The findings reveal that the kupat (rice cake) symbolizes evolving philosophical values—from five moral principles (pre-Islamic) to the five pillars of Islam, and now the embodiment of Pancasila. The ritual strengthens community solidarity and promotes environmental preservation through customary restrictions on forest exploitation. Theoretically, Sidekah Kupat reflects the mechanical solidarity of agrarian societies and functions as a means of social integration amid modernization. Therefore, this tradition remains relevant as a medium for moral, social, and ecological education in contemporary society.